Hysteroscopic salpingosonography: a novel technique for infertile patients - Kapoor, Garima; Bajaj, Bindu; Rani, Usha; Pardeshi, Geeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility is akin to curse in our country. Patients of infertility run from pillar to post to get relief. Government Hospitals in India lie at the tail end of window-shopping of infertility centres by the patients having exhausted all their resources. Patients report without any detailed records, lost reports, coming after long hiatus of having stopped treatment in desperation, making one wonder how to proceed. At the other end are patients who have undergone laparotomy for various reasons like intestinal obstruction, tubercular abdomen, adnexal masses and their tubal status is not very clear on HSG. So, repeat laparoscopy in the former group and performing ab initio in the latter, involves putting the patients to the risk of general anesthesia, injury to internal organs due to anticipated adhesions. Although Hassan’s technique of open trocar entry is well accepted the first port entry, whatever be the mode, is an entry open to risks. Methods: In a selected group of infertile women, a baseline TVS was done on 2/3 day of menses and on the 7/8 day of menstrual cycle hysteroscopy was done which was immediately followed by another transvaginal ultrasound. The descriptive statistics is presented in the form of percentages and appropriate graphs. Results: Among the 54 patients who underwent this procedure, 65% had normal uterine cavity. 18% were referred for IVF. 9.2% conceived post procedure. Conclusions: Successive use of transvaginal ultrasound after hysteroscopy i.e Hysteroscopic sonosalpingography is a useful procedure in a select group of infertile patients.